جهود السيوطي في الدفاع عن السنة والرد على منكريها: دراسة تحليلية في كتاب مفتاح الجنة: Al-Suyūṭī’s Efforts in Defending the Sunnah and Refuting its Deniers: an Analytical Study in the Book Miftāḥ Al-Jannah - Nur Baiti Hidayah; Muhammad Ilyas; Muhid Muhid; Rabiatil Rabiatil; Nabilah Nur Hasanah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study aims to analyze and reveal the efforts of Al-Ḥāfiẓ al-Suyūṭī in defending the Prophetic Sunnah and refuting the misconceptions of its deniers through his book, Miftāḥ al-Jannah fī al-Iḥtijāj bi al-Sunnah. This research employs a descriptive-analytical method, utilizing library research to collect and organize the scientific material. The significance of this study lies in providing a robust scientific response to movements that question the authority of the Sunnah، such as the Quraniyyun and Orientalists, demonstrating that Al-Suyūṭī’s arguments remain vital and capable of addressing contemporary discourses.The study concludes that Al-Suyūṭī successfully constructed a comprehensive defensive strategy for the Prophetic Sunnah and a refutation against its deniers, based on Quranic texts، Prophetic traditions, and the consensus of the Imams. He emphasized that the denial of the Sunnah is not merely a jurisprudential opinion, but rather a contradiction to the "Path of the Believers"—the Companions, the Successors (Tabi'un), and those who followed them in righteousness. Furthermore, Allah ﷻ has commanded folloing their path and made it the way to salvation in this world and the hereafter. He also stressed that rejecting the Sunnah is a deviation from the requirements of obeying the Messenger ﷺ, which is an inseparable part of obeying Allah ﷻ.